تناظر الجمل في الآية الواحدة من القرآن الكريم (المنهاج الرباني)"آية الدَّين مثالاً" إضاءة قرآنية على مفهوم التنمية المستدامة: Symmetry in sentences in one verse of the Holy Qur’an (Al-Minhaj al-Rabbani) “The verse of Debt as an example” Quranic illumination on the concept of sustainable development - Al-Younis, Hanan Ghazi; AL-Rawajfeh, Aiman (SIBAWAYH Arabic Language and Education, 2023)
هدفت هذه الدراسة إلى تطبيق المستوى الثالث من مستويات نظرية المجموعات والتناظر في القرآن الكريم وهو تناظر الجمل أو الكلمات في الآية الواحدة(بداية مع بداية، وبداية مع نهاية)؛ للكشف عن كيفية تطبيق الاحكام الفقهية الخاصة بالمعاملات المالية في الإسلام، حفظ حقوق العباد فيما بينهم، والالتزام بأوامر الله تعالى والابتعاد عن نواهيه، وأستخدمت الدراسة منهجية البحث التحليلي، وتكون مجتمع الدراسة وعينته من آية الدَّين آية رقم (282) من سورة البقرة، واستخدم الباحثان الجملة لتحليل النص القرآني، وقائمة تحليل واحدة أداة للدراسة، وتوصلت الدراسة إلى أن آية الدَّين عبارة عن منهاج مصغر للقرآن الكريم مكتمل العناصر، تضمنت (13) جملة مكتملة المعنى، منها(9)جمل على شكل أوامر و(4) جمل على شكل نواهي، حيث يكون التعلم من الخاص إلى العام، أي أن ما ينطبق على عقد الدَّين ينطبق على العقود الأخرى مثل: عقد البيع، عقد الزواج، عقد الإيجار، وغيرها من العقود، ويوصي الباحثان بربط القرآن الكريم بالمناهج الأخرى، والتركيز على التعليم كوسيلة لتنمية معارف الفرد ومهاراته واتجاهاته؛ الذي بدوره هو أساس التغيير الذي يحقق أمن المجتمع واستقراره، فصلاح المجتمع مرتبط بصلاح أفراده الذين هم أساس التنمية المستدامة. This study aimed at applying the third level of groups theory and symmetry in the Holy Qur’an, which is the symmetry of sentences or words in one verse (beginning with beginning, beginning with end); To reveal how to apply the jurisprudential provisions related to financial transactions in Islam, to preserve the rights of people among themselves, to abide by the commands of God Almighty and to avoid His prohibitions, the study used the analytical research methodology, and the study community and its sample consisted of the verse of religion, verse No. (282) of Surat Al-Baqara, and the researchers used Sentence to analyze the Qur’anic text, a single analysis list tool for the study, The study concluded that Ayat al-Din is a miniature curriculum for the Holy Qur’an complete with elements, which includes (13) sentences with full meaning, including (9) sentences in the form of commands and (4) sentences in the form of prohibitions, where learning is from the specific to the general, meaning that What applies to the debt contract applies to other contracts such as: sale contract, marriage contract, lease contract, and other contracts. The researchers recommend linking the Holy Qur’an to other curricula, and focusing on education as a means of developing the individual’s knowledge, skills, and attitudes. Which in turn is the basis for change that achieves the security and stability of society, as the well-being of society is linked to the well-being of its members, who are the basis of sustainable development. Keywords: symmetry of sentences; The Noble Qur’an (The Divine Curriculum); The verse of Debt